1999
DOI: 10.1002/(sici)1520-6327(1999)41:1<24::aid-arch5>3.0.co;2-r
|View full text |Cite
|
Sign up to set email alerts
|

Ecdysone 20-monooxygenase activity during larval-pupal-adult development of the tobacco hornworm,Manduca sexta

Abstract: Ecdysone 20‐monooxygenase is the insect cytochrome P‐450 dependent steroid hydroxylase system responsible for the conversion of ecdysone to 20‐hydroxyecdysone. Using an in vitro radioassay, the levels of ecdysone 20‐monooxygenase activity were quantified during embryogenesis in the egg, and in the fat body and midgut tissues during the fourth larval, fifth larval, and pupal‐pharate adult stadia of the tobacco hornworm Manduca sexta. Although basal, ecdysone 20‐monooxygenase activity was detected during the lat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 33 publications
(37 reference statements)
0
11
0
Order By: Relevance
“…There is a remarkable correlation between changes in the activity [29,30] and the levels of shd mRNA in the fat body and midgut during the fifth instar and the first 6 days of pupal-adult development ( Figure 2). This suggests that the activity of the Manduca E20MO is strictly dependent on the transcriptional activity, although posttranscriptional control may also occur.…”
Section: Expression Of the Manduca Halloween Genesmentioning
confidence: 99%
“…There is a remarkable correlation between changes in the activity [29,30] and the levels of shd mRNA in the fat body and midgut during the fifth instar and the first 6 days of pupal-adult development ( Figure 2). This suggests that the activity of the Manduca E20MO is strictly dependent on the transcriptional activity, although posttranscriptional control may also occur.…”
Section: Expression Of the Manduca Halloween Genesmentioning
confidence: 99%
“…Furthermore, it has been shown that these increases in activity are the result of de novo enzyme synthesis and coincide with increases in both E20-M activity and its encoding gene, shade. 7,12 Research detailing the role of the cytochrome P-450 steroid hydroxylase E-20M has established its role in the NADPH-dependent conversion of the molting hormone, ecdysone, to its physiologically active form, 20-HE. 3,[16][17][18] Because this activity requires NADPH, and is predominantly associated with the mitochondria of the ecdysone target tissues such as midgut, fatbody, and Malphighian tubules 5,19 an association with the reversible transhydrogenase seems likely.…”
Section: Discussionmentioning
confidence: 99%
“…The nature, regulation, and molecular biology of E20M were elucidated predominantly employing the tobacco hornworm, Manduca sexta, as the model [3][4][5][6][7][8]. Indeed, the developmental impact of E20M was made evident in midgut tissue of the M. sexta fifth larval instar where E20M activity increases 50-fold between days four and five of the stadium and this increase is inextricably tied to the onset of wandering stage behavior [1,8,9]. Moreover, the timing conferred by pulses of 20E was found to be critical to all stages of insect development [1,10].…”
Section: Introductionmentioning
confidence: 99%